Antibody Engineering A Practical Approach - McCafferty,John;Ed. Hoogenboom, H R; Ed (Practical approach series, 169., 1996)
Recombinant DNA techniques have revolutionized the isolation and production of antibodies. This volume describes methods and technologies which will allow the researcher to isolate a new antibody, analyse its properties, format the correct antibody or fragment, and produce sufficient quantities for experimental use. Topics in this volume include: generation and analysis of antibodies; antibody repertoires; antibody screening and selection; measuring antibody affinities; sequence analysis; antibody engineering and production; conversion of rodent antibodies to human antibodies by CDR grafting or guided selection; choosing and optimizing effector functions; preparation and use of antibody-based molecules in eukaryotic and prokaryotic systems; scaling up manufacture; and generation of high-affinity high-specificity human antibodies in appropriate formats. Antibody Engineering is a unique manual of recombinant DNA methods for all those working with antibodies in research, diagnostics, and therapeutics. Each chapter is written by a leading researcher in the field and provides essential background information, fully tested protocols, sample data from using these methods, trouble-shooting comments, and key hints and tips for success.